Energy and water consumption and carbon footprint of school buildings in hot climate conditions. Results from life cycle assessment. (10th September 2018) - Gamarra, A.R.; Istrate, I.R.; Herrera, I.; Lago, C.; Lizana, J.; Lechón, Y.
Abstract: Optimized energy use and water provision in school buildings play an important role in the sustainability performance of municipalities, and are included in the local sustainable energy policies. Hot climate conditions exacerbate the need for the use of cooling devices and are usually associated to water scarcity problems. Additionally, school buildings in these areas are usually lacking good thermal insulation conditions and energy efficiency measures. This work analyses the energy, material and water requirement activities of two schools located in a hot climate area, and evaluates the aggregated energy and water consumption, the water scarcity exacerbation problems, and the associated carbon footprint through Life Cycle Assessment, which allows the quantification of the impacts along the whole value chain of the school activities per student. Additionally, the effects of different improvement measures, such as the implementation of renewable energy sources and the optimization of energy use based on energy efficiency measures, such as changes in the lighting technologies, are quantified. The results show that schools could reduce the fossil energy demand of the building in the operating and maintenance phase per student between 4.89% and 6.03% by means of the implementation of non-renewable heating measures, between 64.06% and 78.98% by means of the implementation of renewable heating solutions, and between 12.05% and 9.54% by means of the implementation of lighting substitution measures. Highlights: School buildings in hot climate areas are usually lacking good thermal insulation conditions and energy efficiency measures. Life Cycle Analysis methodology was used to quantify environmental impacts along the whole of the school activities. Schools could reduce environmental impacts through the application of renewable heating and lighting substitution measures. LCA helps to identify hotspots and modifying consumption practices to achieve the goals of environmental impacts decreasing.